Application of Public Domain Satellite-based DEMs in Geohazard Modeling - Akbari, Abolghasem; Noram Irwan, Ramli; Ngien, S. K.; Reyhane, Azimi (Elsevier Ltd, 2014)
With the invention of Geospatial Information Systems (GIS) and Geohazard computer models, the role of digital elevation model (DEM) has become very important and effective tools in Geohazard modeling. Flood inundation mapping, landslide susceptibility mapping and wind velocity mapping are examples that effectively employ the DEM and its derivatives as one of the important modeling inputs. On the other hand, satellite based DEMs have been growing rapidly in recent years. There are several sources of DEMs available ranging from very coarse to high resolution which provides geospatial data in different scales. This paper describe the specification and applications of public domain satellite-based DEMs including SRTM and ASTER-GDEM which, are globally free. From several applications, the scope is limited to the application of public domain satellite DEMs in flood potential mapping which is considered a widespread Geohazard. From the result, it was found that several advantages were recognized for public domain satellite–based DEMs including ease of accessibility, elimination of institutional bureaucracy, unlimited coverage, adequate spatial resolution, and more importantly, they are available free of charge